Analisis Dampak Penggunaan Gadget Terhadap Tingkat Nyeri Dismenore Pada Remaja Putri Kelas X Di SMAN 2 Kalukku - Manuntungi, Andi Ernawati (Jurnal Ilmiah Amanah Akademika, 2022)
Playing gadgets excessively, especially in most adolescents, can interfere with physical activity, which theoretically by doing regular physical activity or doing sports can produce endorphin hormone, which functions as a natural calming agent produced by the brain, causing a sense of comfort, including when experiencing dysmenorrhea. In addition, there are also many impacts of excessive gadget use, which can disrupt sleep patterns and eating patterns, which can also have an impact on the level of dysmenorrhea pain. The purpose of this study was to determine the impact of gadget use on the level of dysmenorrhea pain in adolescent girls at SMAN 2 kalukku in 2023. The research design used quantitative descriptive analytic with a cross sectional approach. The population of this study were all class X students who were experiencing menstruation and were gadget users as many as 70 people who were taken using simple random sampling which resulted in 41 respondents. The independent variable is the intensity of gadget use with moderate variables namely sleep patterns, physical activity and diet while the dependent variable is the level of dysmenorrhea pain. Based on the results of statistical tests using the Spearman's rho test, the results show that there is a relationship between the variable intensity of gadget use with the level of dysmenorrhea pain with the results (p=0.000). But there is no significant relationship between the variables of sleep patterns, diet, and physical activity to the level of dysmenorrhea pain with an average p value of (p=0.000).